2023
DOI: 10.1101/2023.05.23.23290409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recovery from Amblyopia in Adulthood: A Meta-Analysis

Madison P. Echavarri-Leet,
Hannah H. Resnick,
Daniel A. Bowen
et al.

Abstract: Purpose: The effectiveness of traditional amblyopia therapies is largely restricted to childhood. However, recovery in adulthood is possible following removal or vision-limiting disease of the fellow eye. Study of this phenomenon is currently limited to isolated case reports and a few case series, with reported incidence ranging from 19-77%. We set out to accomplish two distinct goals: (1) define the incidence of clinically meaningful recovery and (2) elucidate the clinical features associated with greater amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Since publishing this article, we have extended our examination of this phenomenon to all published cases to identify clinical factors that facilitate recovery from amblyopia. 1 As Dr. Örnek points out, there are several potential mechanisms at play as we have outlined in a recent review. 2 We are committed to elucidating these mechanisms which hold translational potential for visual recovery beyond amblyopia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since publishing this article, we have extended our examination of this phenomenon to all published cases to identify clinical factors that facilitate recovery from amblyopia. 1 As Dr. Örnek points out, there are several potential mechanisms at play as we have outlined in a recent review. 2 We are committed to elucidating these mechanisms which hold translational potential for visual recovery beyond amblyopia.…”
mentioning
confidence: 99%
“…In our meta-analysis of 101 reported cases with AEVA improvement after FE vision loss (which included this ION data set), multiple regression analysis revealed that FEVA nadir was independently associated with greater grains AEVA. 1 We did not examine durability of AEVA because follow-up duration is highly variable across the few reports that include this information. Data from animal models demonstrate that the functional and structural consequences of amblyopia can be reversed at older ages with temporary FE inactivation with durability even after FE responses have returned to baseline.…”
mentioning
confidence: 99%